Trends in Higher Education and Library Consortia. Issue 5 (4th July 2017) - Machovec, George
ABSTRACT: Public higher education is going through dramatic changes in terms of student demographics, public funding and changing perceptions on the value of higher education. Libraries are embedded in this ecosystem and must adjust to changing requirements and expectations. To help mitigate the impacts from these changes, libraries are collaborating through regional consortia to extend their purchasing power, provide services and do what they can to minimize negative impacts.